The local impact of globalization in South and Southeast Asia offshore business processes in services industries - Lambregts, B. W.; Beerepoot, Niels; Kloosterman, Robert (Abingdon, Oxon New York, NY Routledge, 2016)
"The latest wave of globalization in South and Southeast Asia has been largely services driven, in particular by firms from advanced economies relocating part of their business processes abroad. This has caused profound changes in the international division of labour, and has had correspondingly wide social and economic effects. These new and complex developments cannot be separated from the still evolving outcomes of previous waves of globalisation. This new book takes a close look at how the offshoring of business processes in services industries plays out in South and Southeast Asia, and how this latest wave of globalization both affects societies and is conditioned by their political economies. The book's central aims are threefold. First of all, it aims to draw attention to the outcomes of the global trend of business processes offshoring in services industries in the receiving Asian countries. Its second aim is to assess how the outcomes of this latest wave of globalisation are helping to rebalance relationships at the regional and global levels. Finally, the book assesses the implications of the above for theories of economic development. In particular, it examines to what extent we are seeing evidence of a services-based development trajectory emerging as a real possibility, investigating parallels and differences between the manufacturing- and services-based waves of offshoring. The volume stands out from other books in the field in its exploration of the social and economic outcomes in the cities and countries where services have been located. Based on cutting edge empirical research and original data, the volume offers a state-of-the-art contribution to this growing debate"-- Provided by publisher.
"In the past two decades, several millions of IT-enabled services jobs have been relocated or 'offshored' from the US and Europe to, in particular, low cost economies around the world. Most of these jobs so far have landed in South and South-East Asia, with India and the Philippines receiving the bulk of them. This has caused profound changes in the international division of labour, and has had correspondingly wide social and economic effects. This book examines how this 'next wave in globalization' affects people and places in South and South-East Asia. It brings together twelve case studies from India, the Philippines, China, Hong Kong and Thailand, and explores how and for whom services offshoring creates opportunities, triggers local economic transformations and produces challenges. This book in addition compares how different countries take part in this 'second global shift', investigates service-sector driven economic development from a historical perspective, and engages with the question whether and to what extent services offer a new promising avenue of sustained economic growth for developing countries. It argues that service-led development in developing countries is not easy for all the workers involved, or a guaranteed path to sustained economic development and prosperity. This volume stands out from other books in the field in its exploration of the social and economic outcomes in the cities and countries where services have been located. Based on cutting edge empirical research and original data, the volume offers a state-of-the-art contribution to this growing debate"--Provided by publisher.
Keywords: Offshore outsourcing -- South Asia; Offshore outsourcing -- Southeast Asia; Service industries -- South Asia; Service industries -- Southeast Asia